Thrombolysis in the age of Primary Percutaneous Coronary Intervention: Mini-Review and Meta-analysis of Early PCI - Al Shammeri, Owayed M; Garcia, Lawrence (International Journal of Health Sciences, 2013)
Objective: Primary Percutaneous Coronary Intervention (PCI) is the treatment of choice for ST-segment Elevation Myocardial Infarction (STEMI) if performed within 90 minutes from first medical contact. However, primary PCI is only available for less than 25% of patients with STEMI. Early PCI or Pharmaco-invasive strategy has evolved from facilitated PCI but with more delayed timing from thrombolysis to PCI. Aim: Assess the safety and effectiveness of Early PCI. Patients and Method: We reviewed the data of the available therapy options for patients with STEMI. Then we performed a meta-analysis for all randomized controlled trials of early PCI versus standard therapy Results: Five studies fulfilled our inclusion criteria. Our meta-analysis showed improved cardiovascular events with early PCI compared to standard therapy (odd ratio of 0.54; 95% Confidence interval 0.47-0.7, p<0.001). There were no significant bleeding complications when doing early PCI 4 to 24 hours after successful thrombolysis Conclusion: Early PCI should be done to all STEMI patients within 24 hours after successful thrombolysis. Key words: Pharmacoinvasive strategy, Early PCI, Acute myocardial infarction, Thrombolysis